Photoinduced release of alanine and glutamic acid from (11-oxo-2,3,5,6,7,11-hexahydro-1H-pyrano[2,3-f]pyrido[3,2,1-ij]quinolin-9-yl)methyl cages - Piloto, Ana M. (2012)
In the present communication is described the photoinduced release of L-alanine and L-glutamic acid from (11-oxo-2,3,5,6,7,11-hexahydro-1H-pyrano[2,3-f]pyrido[3,2,1-ij]quinolin-9-yl)methyl cages in methanol/HEPES buffer solution (80:20), under different photolytic conditions, such as the wavelength of irradiation (254, 300, 350 and 419 nm).